Cannabis sativa-mediated synthesis of gold nanoparticles and their biomedical properties. Issue 2 (16th January 2020) - Hameed, Safia; Ali Shah, Sajjad; Iqbal, Javed; Numan, Muhammad; Muhammad, Wali; Junaid, Muhammad; Shah, Sumaira; Khurshid, Razia; Umer, Fazal
Abstract : Nanotechnology describes precision manufacturing of materials at the nano scale. Nanotechnology has a vast range of applications, such as medicines, electronics, biomaterials and energy production. The present research work is a green eco-friendly approach to the production of gold nanoparticles (Au-NPs) by using the plant extract of Cannabis sativa . The appearance of a ruby-red color from a greenish color is the primary indication of the formation of Au-NPs. C. sativa contains some active compounds that were found to be responsible for the reduction of gold and converting it into a bioactive metal. The synthesized Au-NPs were characterized by ultraviolet–visible spectroscopy, high-resolution scanning electron microscopy and Fourier transform infrared spectroscopy. In vitro antimicrobial, cytotoxicity, biocompatibility and enzyme inhibition assays were performed. Notable antimicrobial activities are reported. Bioinspired Au-NPs were found effective against bacterial and fungal strains. A 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay was performed to check the leishmanicidal activity against amastigotes (IC50 : 171·00 ± 2·28 μg/ml) of Leishmania tropica . Brine shrimp lethality was also shown by the bioinspired Au-NPs. Furthermore, substantial protein kinase inhibition was noted.